Fish Feeding System in Aquaponic Media Using Firebase and Internet of Things Based Codular - Santoso, Putra Pratama; Rosmalia, Lia (Prosiding International conference on Information Technology and Business (ICITB), 2023)
The aquaponics system is an agricultural method that integrates fish cultivation with plants in an interrelated system. Where fish are used as a source of nutrition for plants, and plants become natural filters to clean water. Feeding fish is very important because it is the main source of nutrition for fish and has a direct impact on fish health, plants, growth and production. Providing scheduled feed and appropriate doses is very important to maintain the health of fish and the aquaponic ecosystem. Use a 30 liter dryer for catfish and kale plants. Feeding is regulated by the number of servo revolutions, the RTC sensor regulates the feed schedule, the ultrasonic sensor measures water level, and the IR-FC51 sensor measures feed availability. Kodular and Firebase applications as real-time databases are used as tools to create a system interface that can be accessed by users for monitoring water levels and feed availability as well as controlling automatic schedules and feeding doses with the aim of ensuring regular feeding, good and healthy fish growth, reduces feed waste absorbed by plants. This system has additional manually operated facilities to control the water pump and feeding which the user can access in real time via smartphone.Keywords—Aquaponics, Feeding, Automatic Systems, Internet of Things, Smartphones